Controlled aggregation enhances immunomodulatory potential of mesenchymal stromal cell aggregates. (5th April 2021) - Xie, Angela W.; Zacharias, Nicholas A.; Binder, Bernard Y. K.; Murphy, William L.
Abstract: Human mesenchymal stromal cells (MSCs) are promising candidates for cell therapy due to their ease of isolation and expansion and their ability to secrete antiapoptotic, pro‐angiogenic, and immunomodulatory factors. Three‐dimensional (3D) aggregation "self‐activates" MSCs to augment their pro‐angiogenic and immunomodulatory potential, but the microenvironmental features and culture parameters that promote optimal MSC immunomodulatory function in 3D aggregates are poorly understood. Here, we generated MSC aggregates via three distinct methods and compared them with regard to their (a) aggregate structure and (b) immunomodulatory phenotype under resting conditions and in response to inflammatory stimulus. Methods associated with fast aggregation kinetics formed aggregates with higher cell packing density and reduced extracellular matrix (ECM) synthesis compared to those with slow aggregation kinetics. While all three methods of 3D aggregation enhanced MSC expression of immunomodulatory factors compared to two‐dimensional culture, different aggregation methods modulated cells' temporal expression of these factors. A Design of Experiments approach, in which aggregate size and aggregation kinetics were systematically covaried, identified a significant effect of both parameters on MSCs' ability to regulate immune cells. Compared to small aggregates formed with fast kinetics, large aggregates with slow assembly kinetics were more effective at T‐cell suppression and macrophage polarization toward anti‐inflammatory phenotypes. Thus, culture parameters including aggregation method, kinetics, and aggregate size influence both the structural properties of aggregates and their paracrine immunomodulatory function. These findings underscore the utility of engineering strategies to control properties of 3D MSC aggregates, which may identify new avenues for optimizing the immunomodulatory function of MSC‐based cell therapies. Abstract : Mesenchymal stromal cell (MSC) aggregates display augmented immunomodulatory potential that is dependent on aggregate size and formation kinetics. Large, slow‐forming MSC aggregates outperform small, fast‐forming aggregates in their capacity to induce M2 macrophage polarization and suppress T‐cell proliferation. Aggregate size and aggregation kinetics also influence ECM synthesis and packing density, thereby linking aggregation‐dependent structural features to immunomodulatory function in MSC aggregates.